Chemical Composition and Effect of Hydrodistillation Times on the Yield of Essential Oil from Eugenia pyriformis Leaves - Ana Maria Sá Durazzini; Carlos Henrique Marquezini Machado; Cassia Cristina Fernandes; Mayker Lazaro Dantas Miranda (Orbital: The Electronic Journal of Chemistry, 2019)
This study aimed at determining the chemical composition and evaluating the influence of different times of hydrodistillation on the content of essential oil from Eugenia pyriformis (Myrtaceae) leaves. Four extraction times (60, 120, 180 and 240 minutes) were investigated by a completely randomized experimental design. The highest yield of oil was achieved in the 120-minute hydrodistillation time. The main compounds of the oil determined by GC-MS analyses were β-caryophyllene (18.0%), bicyclogermacrene (16.4%), spathulenol (10.0%) and α-cadinol (8.7%).DOI: http://dx.doi.org/10.17807/orbital.v11i5.1221